Frequency and Mortality Risk Factors of Acute Ischemic Stroke in Emergency Department in Burkina Faso. (11th June 2020) - Dabilgou, Alfred Anselme; Dravé, Alassane; Kyelem, Julie Marie Adeline; Ouedraogo, Saïdou; Napon, Christian; Kaboré, Jean
Abstract : Objective . To determine the prevalence of ischemic stroke deaths and their predictive factors in the Emergency Department at Yalgado Ouedraogo University Teaching Hospital (YOUTH). Methodology . This was a retrospective study with an analytical and descriptive focus over a period of three years from January 1, 2015, to December 31, 2017. Results . During the study period, 302 acute ischemic stroke patients with a mean age of 62.2 ± 14.26 years were included. Atrial hypertension was the most common vascular risk factor in 52.5%. On admission, 34.8% of patients had loss of consciousness. The mean time to perform brain CT was 1.5 days. The average length of stay was 4 days. Electrocardiogram, echocardiography, and cervical Doppler were not performed during hospitalization in ED. The mortality rate was 39%, respectively, 37.6% in male and 41.6% in female. The mean age of patients who died in ED was 63.6 ± 13.52 years. Hypertension was the most common vascular risk factors in 54.2% of death. After logistic regression, the predictors of death were past history of heart disease, consciousness disorders, hyperthermia, hyperglycemia on admission, poststroke pneumonia, and urinary tract infection. Conclusions . Acute ischemic stroke was frequent in Emergency Department with high mortality rate. The mortality risk factors were the same than those found in literature. This higher mortality can be avoided by early diagnosis and an adequate management.